Chapter 8: Principles and Practices of Irrigation Management for Vegetables - Eric H. Simonne; Michael D. Dukes; Dorota Z. Haman (EDIS, 2019)
This section contains basic information on vegetable water use and irrigation management, along with some references on irrigation systems. This document is AE260, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.